The future of lasers in electronics - Schmidt, Michael; Eßer, G. (ICALEO 2003 - 22nd International Congress on Applications of Laser and Electro-Optics, Congress Proceedings, 2003)
Today laser technology is already used in many production steps in electronic and micro mechanic manufacturing. From photolithographic imaging of wafers with excimer lasers up to laser welding of electrical interconnects the laser today has a widespread field of application. The article offers a closer look inside the areas semiconductor and interconnect. Beginning with current market numbers, different application examples are pointed out and the future role of lasers therein is discussed. Trends like process parallelization, modelocked lasers or fiber lasers are pointed out. Neither a complete overview on current applications nor a quantitative measure of the future potential of laser based processes will be given. The aim of the article is to provide a basis to encourage a fruitful discussion.
Created from Fastlane, Scopus look-up
Keywords: Interconnect; MEMS; Micro mechanics; Micro technology; MOEMS; Semiconductor; Trends